OK, now do this one:


Hey, hey, hey!  What, am I sick or something?  Well, yeah, I am.  But, that's another story.  Luckily, there is a much easier way to deal with this critter.

Let's look back at the ones we've already done:

(x^2)(x^3) = x^(2+3) = x^5
(w^3)(w^4) = w^(3+4) = w^7
(y)(y^6) = y^(1+6) = y^7

See why it works?  If you understand this thing, then you'll always know when you can use it -- and when you can't!

Here's the official rule:

exponent rule #1:  (a^n)(a^m) = a^(n+m)


Simplify    (x^43)(x^106)